A natural probioenzyme strategy as an effective alternative to antibiotics against multidrug-resistant Klebsiella pneumoniae in broilers: Benefits for growth, immunity, and organ health - Atef A. Salim; Nehal A. Naena; Mofid Y. Gouda; Safaa M. Shabana; Amr I. Zaineldin (PLoS ONE, 2026)
The rise of multidrug-resistant Klebsiella pneumoniae poses a serious threat to poultry health and food safety, necessitating sustainable alternatives to antibiotics. Our investigation began with an epidemiological survey of broiler samples, which detected K. pneumoniae in 8.88% (8/90) of cases. Among these isolates, over 60% were multidrug-resistant. Antimicrobial susceptibility testing showed bacterial resistance to penicillin G (100%) but complete sensitivity to colistin sulphate (100%). Molecular analysis further revealed a high prevalence of key resistance genes ( tet A [87.5%] and bla TEM [100%]) and virulence factors ( fim H [100%] and tra T [62.5%]), while all isolates were confirmed by amplification of the conserved 16S-23S ITS region. We then evaluated a novel probioenzyme formulation as a dietary intervention in a 35-day broiler trial. Birds challenged with K. pneumoniae were supplemented with either probioenzyme (1 g/kg feed) or treated with colistin sulfate (antibiotic control). Probioenzyme supplementation resulted in growth performance enhancement (final body weight, weight gain, specific growth rate) comparable or superior to, the antibiotic-treated group ( P < 0.05 ). The probioenzyme in KPT restored FCR to levels matching the unchallenged (CT) and antibiotic-treated groups (KAT). Histopathological analysis showed complete restoration of intestinal villus architecture, pulmonary integrity, and hepatic cytoprotection in the probioenzyme group, matching antibiotic efficacy. Furthermore, probioenzyme enhanced systemic antioxidant capacity (catalase, superoxide dismutase, total antioxidant capacity) and innate immune response (lysozyme activity) by day 35 ( P < 0.05 ). These findings demonstrate that dietary probioenzyme is a viable alternative to antibiotics, effectively mitigating K. pneumoniae infection while improving growth, organ health, and immune competence without contributing to antimicrobial resistance. This strategy supports sustainable poultry production and aligns with global efforts to reduce antibiotic reliance.